The Production and Dissemination of Agricultural Knowledge at U.S. Research Universities - 이유환 (한국농촌경제연구원, 2017)
This paper analyzes food and agriculturally-related knowledge production and transfer for 114 top-tier U.S. research universities from 1993 to 2015, to understand the role of the Land-Grant universities in promoting commercial innovation and regional economic development in this sector. We utilize two empirical methods: (1) a panel analysis of the knowledge production function (KPF) for research productivity and (2) an analysis of variance (ANOVA) for the role of the Land-Grant universities in such knowledge production. Output of research publications exhibits decreasing returns to scale for all sub-fields, but cost advantages and mean research (gestation) lags vary by sub-field. The mean number of research publications by the Land-Grant universities is much higher than non Land-Grant universities, especially in the Central region of the U.S. These results demonstrate how specialization by Land-Grant universities in agricultural R&D contributes to commercial innovation within a diffuse yet regionalized industry. Moreover, the main context and results of this paper would suggest some important implications to the study of the system of food and agricultural R&D and commercial innovations in Korea.
Keywords: agricultural R&D; Land-Grant university; knowledge production function; public domain; technology transfer and dissemination; polynomial distributed lags; agricultural R&D; Land-Grant university; knowledge production function; public domain; technology transfer and dissemination; polynomial distributed lags